Progress in personalized immunotherapy for patients with brain metastasis - Lalit Patel; Nikola Kolundzic; Malak Abedalthagafi (npj Precision Oncology)
Abstract Brain metastasis leads to poor outcomes and CNS injury, significantly reducing quality of life and survival rates. Advances in understanding the tumor immune microenvironment have revealed the promise of immunotherapies, which, alongside surgery, chemotherapy, and radiation, offer improved survival for some patients. However, resistance to immunotherapy remains a critical challenge. This review explores the immune landscape of brain metastases, current therapies, clinical trials, and the need for personalized, biomarker-driven approaches to optimize outcomes.